The fight for free speech : ten cases that define our First Amendment freedoms - Rosenberg, Ian (New York University Press, 2021)
"Media lawyer Ian Rosenberg distills the spectrum of free speech law down to ten critical issues. Each chapter in this book focuses on a contemporary free speech question--from student walkouts for gun safety to Samantha Bee's expletives, from neo-Nazis marching in Charlottesville to the muting of adult film star Stormy Daniels-- and then identifies, unpacks, and explains the key Supreme Court case that provides the answers"--Provided by the publisher.